KINERJA PEGAWAI KANTOR KECAMATAN ILIR BARAT I KOTA PALEMBANG DALAM PENYELENGGARAAN PELAYANAN PUBLIK - Wijaya, Raden (Jurnal Politik Pemerintahan Dharma Praja, 2019)
Employee Performance of Ilir Barat I District Office in Palembang City in the Implementation of Public Services. This study aims to determine the level of performance of service units and determine the quality of service on a regular basis as an ingredient for establishing policies in order to improve the quality of public services. In addition, this study also aims to determine how the performance of the District Government in the Implementation of Public Services in Ilir Barat I Subdistrict, Palembang City. The method used in this study is quantitative descriptive research. Data collection techniques used are using observations, interviews and questionnaires. Questionnaire instruments in this study using the measurement scale used is an ordinal scale with a type of Likert scale. Before the research instrument is used, validity and reliability tests are conducted to determine the extent to which instruments can be trusted. The interpretation of the respondent’s answers was measured by a score that weighs 1 to 5, which means strongly disagreeing to strongly agree. The analytical method used in this study is Factor Analysis. The results show that the most dominant factors are Quality, Responsiveness and Productivity. Thus, based on the perception of Ilir Barat I District, these factors are determinants of achieving excellent service. Meanwhile, the lowest dominant factor is the Accountability factor. Thus the employees of the Ilir Barat I District office are responsible for carrying out their duties not to violate the rules but only to carry out their duties without creativity and motivation in order to achieve excellent service.